Politik Pangan: Ketahanan Nasional Dan Tren Diplomasi Kekinian - Siti Masruroh; Irham Bashori Hasba; Rasyid Musdin (Balobe Law Journal, 2022)
Introduction: Food availability is the main starting point in supporting the country's economy. Scarcity of food will have an impact on economic stability in each sector. Countries with superior availability of materials and food production will certainly have absolute advantages, including the state's freedom to determine materials and food production, determine prices, and trade commodities on an international scale. Therefore, food is often a medium of diplomacy and a bargaining power over other countries.Purposes of the Research: Analysis tool on food as part of national security on the one hand, and food as a diplomatic tool between countries on the other.Methods of the Research: This study uses a normative legal research method with a statutory approach, a theoretical approach, and an analytical approach. Primary materials using Law no. 24 of 2000 and the General Agreement on Tariffs and Trade (GATT). Secondary materials in the form of journals and documents that support research.Results of the Research: It is at the heart of a research report because a finding is what the reader is actually looking for. The findings component does not have to present all the things that are found in the research, it is presented that the findings are relevant to the nature of this research. For example: The results show that or The findings of this study prove that businesses that reached their dominant position before the recession had a significant advantage over small businesses. However, they cannot be compelled to act on the same basis for very long, which is why a more US-like model would be useful for controlling some of these business behaviors.